High-temperature-resistant anti-corrosion polytetrafluoroethylene material and preparation method thereof

By adding fluorinated modified graphene oxide, aluminum powder, modified silicon carbide fiber, silane modified nano-silica and other fillers to the polytetrafluoroethylene material, the performance of the material is improved, and the high temperature of polytetrafluoroethylene material is solved and mechanical strength and stability issues in corrosion environments have achieved higher high temperature corrosion resistance and long-term stability.

CN119410088AInactive Publication Date: 2025-02-11GUANGDONG ENZINIER SPECIAL PLASTICS CO LTD

Patent Information

Application Number
CN202510012054.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polytetrafluoroethylene materials have low mechanical strength and large thermal expansion coefficient in high temperature and corrosion environments, which can easily lead to pipeline deformation, and may surface aging during long-term use, affecting service life.

Method used

50 to 60 parts of polytetrafluoroethylene, 5 to 10 parts of fluorinated modified graphene oxide, 3 to 5 parts of aluminum powder, 5 to 8 parts of modified silicon carbide fiber, 3 to 5 parts of silane modified nano-silicon dioxide , a combination of 2 to 3 parts of polyphenylene sulfide, 2 to 3 parts of polyimide, 0.3 to 0.5 parts of dispersant and 0.5 to 1 part of antioxidant, improves the comprehensive performance of the material through the synergistic action of a variety of fillers.

Benefits of technology

It significantly improves the mechanical strength, heat conduction path, toughening and high temperature corrosion resistance of polytetrafluorovinyl composite materials, ensuring the long-term stability and reliability of the material in high temperature and complex chemical environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410088A_ABST
    Figure CN119410088A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer plastic materials, and particularly relates to a high-temperature-resistant anti-corrosion polytetrafluoroethylene material and a preparation method thereof. The polytetrafluoroethylene is prepared from the following raw materials in parts by weight: 50 to 60 parts of polytetrafluoroethylene, 5 to 10 parts of fluorinated modified graphene oxide, 3 to 5 parts of aluminum powder, 5 to 8 parts of modified silicon carbide fiber, 3 to 5 parts of silane modified nano silicon dioxide, 2 to 3 parts of polyphenylene sulfide, 2 to 3 parts of polyimide, 0.5 to 0.8 part of dispersing agent and 0.5 to 1 part of antioxidant. The heat conduction performance and the interface bonding force are improved through the fluorinated modified graphene oxide, the impact resistance and the wear resistance are enhanced through the silicon carbide fibers, and the corrosion resistance and the wear resistance are improved through the aluminum powder; silane modified silicon dioxide enhances the mechanical property of the composite material by improving the dispersity of the filler, and PPS and PI interact with the surface of the filler through polar groups in molecular chains, so that the interface strength is improved, and the toughness and the thermal stability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer plastic materials, and in particular relates to a high temperature resistant and corrosion resistant polytetrafluoroethylene material and a preparation method thereof. Background Art

[0002] Polytetrafluoroethylene (PTFE) is a polymer compound formed by the polymerization of tetrafluoroethylene and belongs to the family of fluorinated polymers. Due to its unique chemical properties and excellent performance, PTFE is widely used in chemical, electronic, electrical and pharmaceutical fields, especially in harsh environments that require high temperature resistance and corrosion resistance. PTFE usually appears as a white waxy solid with an extremely low friction coefficient, extremely high anti-adhesion, and excellent chemical stability. The melting point of PTFE is about 327°C, and it can work stably for a long time in a wide temperature range of -200°C to 260°C, and can still maintain good mechanical properties at high temperatures. Its surface energy is extremely low and can resist almost all chemical reagents, including strong acids, strong alkalis and organic solvents. The surface of PTFE is very smooth and has an extremely low friction coefficient, which is suitable for fluid conveying pipeline applications. PTFE is non-toxic and harmless and is suitable for use in medical and pharmaceutical environments. In the pharmaceutical industry, the delivery of liquid medicine is crucial to ensure the quality of medicine. Although traditional liquid medicine delivery pipeline materials such as stainless steel have good mechanical strength and corrosion resistance, they still have some limitations under certain specific conditions. Although stainless steel has good corrosion resistance to most chemicals, it may be corroded by certain strong acids, alkalis or special organic solvents, affecting the purity and safety of the liquid medicine. Stainless steel pipes need to be thoroughly cleaned and disinfected after use to prevent cross contamination, which is time-consuming and laborious. In addition, stainless steel may not be able to completely remove some difficult-to-clean residues. Therefore, polytetrafluoroethylene pipes have begun to be widely used in liquid medicine delivery, especially in the transportation of highly corrosive and high-purity liquids. However, the prior art still has the following major defects when applying polytetrafluoroethylene to liquid medicine delivery pipeline materials: although PTFE has excellent chemical stability and high temperature resistance, its mechanical strength is relatively low; PTFE has a large thermal expansion coefficient, which can easily cause pipeline deformation or loosening of connection parts when the temperature changes drastically, affecting the long-term stability of the pipeline; PTFE materials may experience surface aging during long-term use, especially in high temperature and ultraviolet light environments, affecting their service life. Therefore, in response to the above problems, it is extremely necessary to develop a polytetrafluoroethylene material that is effectively resistant to high temperatures, corrosion-resistant and can be used stably for a long time. Summary of the invention

[0003] In view of the defects of the prior art, the object of the present invention is to provide a high temperature resistant and corrosion resistant polytetrafluoroethylene material and a preparation method thereof.

[0004] The technical effect described in the present invention is achieved through the following technical scheme: a high temperature resistant and corrosion resistant polytetrafluoroethylene material, which comprises the following raw materials in parts by weight: 50 to 60 parts of polytetrafluoroethylene, 5 to 10 parts of fluorinated modified graphene oxide, 3 to 5 parts of aluminum powder, 5 to 8 parts of modified silicon carbide fiber, 3 to 5 parts of silane modified nano-silicon dioxide, 2 to 3 parts of polyphenylene sulfide, 2 to 3 parts of polyimide, 0.3 to 0.5 parts of dispersant and 0.5 to 1 parts of antioxidant.

[0005] Preferably, the dispersant is any one of polyvinyl alcohol, polyacrylic acid and sodium dodecylbenzene sulfonate.

[0006] Preferably, the antioxidant is any one of tert-butylhydroquinone, tris(2,4-di-tert-butylphenyl)phosphate and 2,6-di-tert-butylphenol.

[0007] Preferably, the specific preparation steps of the fluorinated modified graphene oxide are as follows: A1: Add graphite powder to a flask, slowly add concentrated sulfuric acid and concentrated phosphoric acid, control the temperature at 0-5°C, stir and disperse evenly, raise the temperature to 10°C, and then slowly add potassium permanganate. After the addition is complete, raise the temperature to 35-40°C, stir and react for 12-24 hours, slowly add deionized water to dilute, then add hydrogen peroxide, centrifuge, repeat washing with deionized water and 1M HCl solution for 3 times, and vacuum dry at 60°C for 12-24 hours to obtain graphene oxide; A2: The graphene oxide prepared in step A1 is dispersed in anhydrous ethanol, and after being dispersed uniformly by ultrasonic treatment, hydrogen fluoride gas is introduced, and the mixture is reacted at 0-5° C. for 3-6 hours, and the mixture is washed with deionized water until the pH value is neutral, and dried at 60-80° C. for 12-24 hours to obtain fluorinated modified graphene oxide; Preferably, in step A1, the ratio of the amount of graphite powder, concentrated sulfuric acid and concentrated phosphoric acid is 1g:20-25mL:2-3mL; the ratio of the amount of potassium permanganate, deionized water, hydrogen peroxide and graphite powder is 3g:80-100mL:3-4mL:1g; Preferably, in step A2, the ratio of the amount of graphene oxide to anhydrous ethanol is 2-5 mg:2 mL; the ratio of the amount of hydrogen fluoride gas to graphene oxide is 100-200 mL:1 g.

[0008] Preferably, the specific preparation steps of the silane-modified nano-silica are as follows: B1: Add nano-silica to anhydrous ethanol, and perform ultrasonic dispersion treatment at 100-200W for 30-60min to obtain a nano-silica dispersion; add γ-glycidyloxypropyltrimethoxysilane to anhydrous ethanol, stir and mix evenly, then slowly drop deionized water and acetic acid, and stir and react at 200-300rpm for 10-30min to obtain a coupling agent solution; B2: Slowly add the coupling agent solution prepared in step B1 to the nano-silica dispersion prepared in step B1, stir at 300-500 rpm for 12 hours at room temperature, centrifuge, wash with deionized water 5 times, and vacuum dry at 60-80° C. for 12-24 hours to obtain silane-modified nano-silica; Preferably, in step B1, the ratio of the amount of the nano-silicon dioxide to anhydrous ethanol is 1 g: 40-50 mL; the ratio of the amount of γ-glycidyloxypropyltrimethoxysilane, anhydrous ethanol, deionized water and acetic acid is 1 g: 15-20 mL: 0.5-0.6 mL: 0.04-0.05 mL; Preferably, in step B2, the volume ratio of the coupling agent solution to the nano-silicon dioxide dispersion is 0.02-0.03:1.

[0009] Preferably, the specific preparation steps of the modified silicon carbide fiber are as follows: C1: Add 3-aminopropyltriethoxysilane to deionized water, stir and mix evenly, adjust the pH to 4-5, and obtain a coupling agent solution with a concentration of 1-2wt%; soak the silicon carbide fiber in the coupling agent solution and stir for 30-60 minutes; C2: centrifuging the silicon carbide fiber treated in step C1, washing, filtering, drying at 60-120° C. for 12 h, then heat treating at 120-150° C. for 8-12 h, and cooling to room temperature to obtain modified silicon carbide fiber; Preferably, in step C1, the ratio of the amount of the silicon carbide fiber to the coupling agent solution is 1 g: 30-50 mL.

[0010] Preferably, another aspect of the present invention is to provide a method for preparing a high temperature resistant and corrosion resistant polytetrafluoroethylene material, and the specific preparation steps are as follows: Ⅰ: drying the aluminum powder at 60-80°C for 1-2 hours, then heating it at 300-400°C for 1-2 hours, and naturally cooling it to room temperature to obtain pretreated aluminum powder; II: polytetrafluoroethylene, fluorinated modified graphene oxide, modified silicon carbide fiber, silane modified nano-silica, antioxidant, dispersant and pre-treated aluminum powder are sequentially added into the ball mill, polyphenylene sulfide and polyimide are added into the ball mill in three batches, and mixed at 200-300 rpm for 30-60 min; III: Pour the mixed raw materials in step II into a mold, heat to 150-200°C, apply a pressure of 10-15 MPa, maintain for 5-10 minutes, naturally cool to room temperature at room temperature, and then cure at 200-250°C for 1-2 hours to obtain a polytetrafluoroethylene material.

[0011] The beneficial effects of the present invention are as follows: The present invention significantly improves the comprehensive performance of polytetrafluoroethylene (PTFE)-based composite materials through the synergistic effect of multiple fillers, especially in the optimization of mechanical strength, heat conduction path, toughening and high temperature corrosion resistance. First, fluorinated modified graphene oxide (FGO) significantly improves the compatibility with the PTFE matrix by introducing fluorine atoms, and the non-polar-non-polar interaction between the fluorine atoms on its surface and the PTFE matrix enhances the interfacial bonding force, thereby improving the mechanical strength of the composite material. FGO itself has high thermal conductivity, can optimize the heat conduction path, and further improve the high temperature resistance of the composite material. Silicon carbide fiber constructs a continuous thermal conductive network in the composite material, further improving the thermal conductivity of the material, and its high strength and high modulus make the composite material outstanding in impact resistance, especially under high temperature conditions, silicon carbide fiber effectively inhibits crack propagation through uniform distribution and fiber structure, thereby significantly enhancing the high temperature resistance and impact resistance of the composite material; the reinforcing effect of silicon carbide fiber comes from both the improvement of wear resistance brought by its hardness and its use as a structural reinforcement fiber, which significantly improves the crack resistance and mechanical stability of the composite material. Aluminum powder provides good corrosion resistance for composite materials through the aluminum oxide protective film formed on the surface, preventing oxidation and maintaining stability in high temperature environments. In addition, aluminum powder can effectively disperse the stress in the composite material, thereby slowing down wear and improving wear resistance and impact resistance to a certain extent. Although aluminum powder itself has a low hardness, its characteristics of dispersing stress and improving material toughness help improve the overall durability of the composite material.

[0012] The present invention utilizes silane-modified nano-silicon dioxide to enhance the interfacial bonding force between the filler and the PTFE matrix, thereby improving the dispersibility of the filler, thereby improving the structural stability of the composite material. Although its hardness and strength itself have limited contributions, under the synergistic effect with silicon carbide fiber, silane-modified silicon dioxide effectively improves the wear resistance and mechanical strength of the material, especially under high temperature conditions, enhancing the overall performance of the composite material. Polyphenylene sulfide (PPS) and polyimide (PI) are used as toughening agents, and the polar groups in their molecular chains interact with the functional groups on the surface of the filler (fluorine groups of FGO and hydroxyl groups of silane-modified silicon dioxide) through dipole-dipole interactions, thereby enhancing the interfacial bonding force; the molecular chains of PPS and PI can absorb the stress caused by the hard filler (silicon carbide fiber), thereby effectively alleviating the brittleness problem caused by the filler, and improving the impact strength and toughness of the composite material, especially under high temperature environment, the toughening effect of PPS and PI helps to maintain the excellent mechanical properties of the material; in addition, the thermal expansion coefficients of PPS and PI are close to those of the PTFE matrix, which helps to reduce the internal stress concentration caused by temperature changes, thereby improving the thermal stability of the composite material.

[0013] In summary, the synergistic effect of various fillers significantly improves the comprehensive performance of the composite material. Fluorinated modified graphene oxide improves thermal conductivity and interface bonding strength, silicon carbide fiber enhances impact resistance and wear resistance, and aluminum powder improves corrosion resistance and wear resistance through surface protective film; silane-modified silica improves the mechanical properties of the composite material by improving filler dispersion, and PPS and PI interact with the filler surface through polar groups in the molecular chain to improve interface strength, toughness and thermal stability; the synergistic effects of the composite material's advantages in various performance aspects overcome the shortcomings of the traditional PTFE matrix and ensure its long-term stability and reliability in high temperature and complex chemical environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0015] Figure 1 It is a graph showing the acid resistance test results of the polytetrafluoroethylene materials prepared in Example 2 of the present invention and Comparative Examples 1 to 4; Figure 2 It is a graph showing the alkali resistance test results of the polytetrafluoroethylene materials prepared in Example 2 of the present invention and Comparative Examples 1 to 4; Figure 3 It is a graph showing the heat resistance test results of the polytetrafluoroethylene materials prepared in Example 2 of the present invention and Comparative Examples 1 to 4. DETAILED DESCRIPTION

[0016] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that, unless otherwise specified, the raw materials involved in the present invention are purchased through conventional commercial channels.

[0017] Example 1: A high temperature resistant and corrosion resistant polytetrafluoroethylene material, which comprises the following raw materials in parts by weight: 50 parts of polytetrafluoroethylene, 5 parts of fluorinated modified graphene oxide, 3 parts of aluminum powder, 5 parts of modified silicon carbide fiber, 3 parts of silane modified nano-silicon dioxide, 2 parts of polyphenylene sulfide, 2 parts of polyimide, 0.5 parts of dispersant and 0.5 parts of antioxidant.

[0018] The specific preparation steps of fluorinated modified graphene oxide are as follows: A1: Add 5g of graphite powder to a flask, slowly add 100mL of concentrated sulfuric acid and 10mL of concentrated phosphoric acid, control the temperature to 0℃, stir and disperse evenly, raise the temperature to 10℃, and then slowly add 15g of potassium permanganate. After the addition is complete, raise the temperature to 35℃, stir and react for 24h, slowly add 400mL of deionized water to dilute, then add 15mL of hydrogen peroxide, centrifuge, repeat washing with deionized water and 1M HCl solution for 3 times, and vacuum dry at 60℃ for 12h to obtain graphene oxide; A2: 1000 mg of graphene oxide prepared in step A1 was dispersed in 1000 mL of anhydrous ethanol, and after being dispersed evenly by ultrasonic treatment, 100 mL of hydrogen fluoride gas was introduced, and the mixture was reacted at 0°C for 3 h, washed with deionized water until the pH value was neutral, and dried at 60°C for 24 h to obtain fluorinated modified graphene oxide; The specific preparation steps of silane-modified nano-silica are as follows: B1: Add 10g of nano-silica to 400mL of anhydrous ethanol, and perform ultrasonic dispersion treatment at 100W for 60min to obtain a nano-silica dispersion; add 1g of γ-glycidyloxypropyltrimethoxysilane to 15mL of anhydrous ethanol, stir and mix evenly, then slowly drop 0.5mL of deionized water and 0.04mL of acetic acid, and stir and react at 200rpm for 30min to obtain a coupling agent solution; B2: Slowly add 8 mL of the coupling agent solution prepared in step B1 to 400 mL of the nano-silica dispersion prepared in step B1, stir at 300 rpm for 12 h at room temperature, centrifuge, wash with deionized water 5 times, and vacuum dry at 60° C. for 24 h to obtain silane-modified nano-silica; The specific preparation steps of modified silicon carbide fiber are as follows: C1: Add 2g of 3-aminopropyltriethoxysilane to 200mL of deionized water, stir and mix evenly, adjust the pH to 5, and obtain a coupling agent solution with a concentration of 1wt%; soak 5g of silicon carbide fiber in 150mL of the coupling agent solution and stir for 30min; C2: centrifuging the silicon carbide fiber treated in step C1, washing, filtering, drying at 60° C. for 12 h, and then heat treating at 120° C. for 12 h, and cooling to room temperature to obtain modified silicon carbide fiber; The specific preparation steps of polytetrafluoroethylene materials are as follows: Ⅰ: drying the aluminum powder at 60°C for 2h, then heating it at 300°C for 2h, and naturally cooling it to room temperature to obtain pretreated aluminum powder; II: polytetrafluoroethylene, fluorinated modified graphene oxide, modified silicon carbide fiber, silane modified nano-silica, tert-butyl hydroquinone, polyvinyl alcohol and pretreated aluminum powder were added to the ball mill in sequence, polyphenylene sulfide and polyimide were added to the ball mill in three batches, and mixed at 200 rpm for 60 min; III: Pour the mixed raw materials in step II into a mold, heat to 150°C, apply a pressure of 10 MPa, maintain for 10 minutes, naturally cool to room temperature at room temperature, and then cure at 200°C for 2 hours to obtain a polytetrafluoroethylene material.

[0019] Example 2: A high temperature resistant and corrosion resistant polytetrafluoroethylene material, which comprises the following raw materials in parts by weight: 60 parts of polytetrafluoroethylene, 8 parts of fluorinated modified graphene oxide, 4 parts of aluminum powder, 7 parts of modified silicon carbide fiber, 4 parts of silane modified nano-silicon dioxide, 2.5 parts of polyphenylene sulfide, 2.5 parts of polyimide, 0.6 parts of dispersant and 0.8 parts of antioxidant.

[0020] The specific preparation steps of fluorinated modified graphene oxide are as follows: A1: Add 5g of graphite powder to a flask, slowly add 120mL of concentrated sulfuric acid and 12mL of concentrated phosphoric acid, control the temperature at 4°C, stir and disperse evenly, raise the temperature to 10°C, and then slowly add 15g of potassium permanganate. After the addition is complete, raise the temperature to 38°C, stir and react for 20h, slowly add 450mL of deionized water to dilute, then add 18mL of hydrogen peroxide, centrifuge, repeat washing with deionized water and 1M HCl solution for 3 times, and vacuum dry at 60°C for 20h to obtain graphene oxide; A2: 1000 mg of graphene oxide prepared in step A1 was dispersed in 800 mL of anhydrous ethanol, and after being dispersed evenly by ultrasonic treatment, 160 mL of hydrogen fluoride gas was introduced, and the mixture was reacted at 4°C for 5 h, washed with deionized water to a neutral pH, and dried at 70°C for 20 h to obtain fluorinated modified graphene oxide; The specific preparation steps of silane-modified nano-silica are as follows: B1: Add 10g of nano-silica to 480mL of anhydrous ethanol, and perform ultrasonic dispersion treatment at 150W for 50min to obtain a nano-silica dispersion; add 1g of γ-glycidyloxypropyltrimethoxysilane to anhydrous ethanol, stir and mix evenly, then slowly dropwise add 0.55mL of deionized water and 0.045mL of acetic acid, and stir and react at 250rpm for 20min to obtain a coupling agent solution; B2: Slowly add 12 mL of the coupling agent solution prepared in step B1 to 450 mL of the nano-silica dispersion prepared in step B1, stir at 400 rpm for 12 h at room temperature, centrifuge, wash with deionized water 5 times, and vacuum dry at 70° C. for 20 h to obtain silane-modified nano-silica; The specific preparation steps of modified silicon carbide fiber are as follows: C1: Add 4.5g of 3-aminopropyltriethoxysilane to 300mL of deionized water, stir and mix evenly, adjust the pH to 4.5, and obtain a coupling agent solution with a concentration of 1.5wt%; soak 5g of silicon carbide fiber in 230mL of the coupling agent solution and stir for 50min; C2: centrifuging the silicon carbide fiber treated in step C1, washing, filtering, drying at 110° C. for 12 h, and then heat treating at 140° C. for 10 h, and cooling to room temperature to obtain modified silicon carbide fiber; The specific preparation steps of polytetrafluoroethylene materials are as follows: Ⅰ: drying the aluminum powder at 70°C for 1.5h, then heating it at 350°C for 1.5h, and naturally cooling it to room temperature to obtain pretreated aluminum powder; II: polytetrafluoroethylene, fluorinated modified graphene oxide, modified silicon carbide fiber, silane-modified nano-silica, tris(2,4-di-tert-butylphenyl) phosphate, sodium dodecylbenzene sulfonate and pretreated aluminum powder were added to the ball mill in sequence, polyphenylene sulfide and polyimide were added to the ball mill in three batches, and mixed at 250 rpm for 50 min; III: Pour the mixed raw materials in step II into a mold, heat to 180°C, apply a pressure of 14 MPa, maintain for 8 minutes, naturally cool to room temperature at room temperature, and then cure at 240°C for 1.5 hours to obtain a polytetrafluoroethylene material.

[0021] Example 3: A high temperature resistant and corrosion resistant polytetrafluoroethylene material, which comprises the following raw materials in parts by weight: 55 parts of polytetrafluoroethylene, 10 parts of fluorinated modified graphene oxide, 5 parts of aluminum powder, 8 parts of modified silicon carbide fiber, 5 parts of silane modified nano-silicon dioxide, 3 parts of polyphenylene sulfide, 3 parts of polyimide, 0.8 parts of dispersant and 1 part of antioxidant.

[0022] The specific preparation steps of fluorinated modified graphene oxide are as follows: A1: Add 5g of graphite powder to a flask, slowly add 125mL of concentrated sulfuric acid and 15mL of concentrated phosphoric acid, control the temperature at 5°C, stir and disperse evenly, raise the temperature to 10°C, and then slowly add 15g of potassium permanganate. After the addition is complete, raise the temperature to 40°C, stir and react for 12h, slowly add 500mL of deionized water to dilute, then add 20mL of hydrogen peroxide, centrifuge, repeat washing with deionized water and 1M HCl solution for 3 times, and vacuum dry at 60°C for 24h to obtain graphene oxide; A2: 1000 mg of graphene oxide prepared in step A1 was dispersed in 400 mL of anhydrous ethanol, and after being dispersed evenly by ultrasonic treatment, 200 mL of hydrogen fluoride gas was introduced, and the mixture was reacted at 5°C for 3 h, washed with deionized water until the pH value was neutral, and dried at 80°C for 12 h to obtain fluorinated modified graphene oxide; The specific preparation steps of silane-modified nano-silica are as follows: B1: Add 10g of nano-silica to 500mL of anhydrous ethanol, and perform ultrasonic dispersion treatment at 200W for 30min to obtain a nano-silica dispersion; add 1g of γ-glycidyloxypropyltrimethoxysilane to 20mL of anhydrous ethanol, stir and mix evenly, then slowly drop 0.6mL of deionized water and 0.05mL of acetic acid, and stir and react at 300rpm for 10min to obtain a coupling agent solution; B2: Slowly add 15 mL of the coupling agent solution prepared in step B1 to 500 mL of the nano-silica dispersion prepared in step B1, stir at 500 rpm for 12 h at room temperature, centrifuge, wash with deionized water 5 times, and vacuum dry at 80° C. for 12 h to obtain silane-modified nano-silica; The specific preparation steps of modified silicon carbide fiber are as follows: C1: Add 6g of 3-aminopropyltriethoxysilane to 300mL of deionized water, stir and mix evenly, adjust the pH to 4, and obtain a coupling agent solution with a concentration of 2wt%; soak 5g of silicon carbide fiber in 250mL of the coupling agent solution and stir for 60min; C2: centrifuging the silicon carbide fiber treated in step C1, washing, filtering, drying at 120° C. for 12 h, and then heat treating at 150° C. for 8 h, and cooling to room temperature to obtain modified silicon carbide fiber; The specific preparation steps of polytetrafluoroethylene materials are as follows: Ⅰ: drying the aluminum powder at 80°C for 1 hour, then heating it at 400°C for 1 hour, and naturally cooling it to room temperature to obtain pretreated aluminum powder; II: polytetrafluoroethylene, fluorinated modified graphene oxide, modified silicon carbide fiber, silane-modified nano-silica, 2,6-di-tert-butylphenol, polyacrylic acid and pretreated aluminum powder were added to the ball mill in sequence, polyphenylene sulfide and polyimide were added to the ball mill in three batches, and mixed at 300 rpm for 30 min; III: Pour the mixed raw materials in step II into a mold, heat to 200°C, apply a pressure of 15 MPa, maintain for 5 minutes, naturally cool to room temperature at room temperature, and then cure at 250°C for 1 hour to obtain a polytetrafluoroethylene material.

[0023] Comparative Example 1: The operation of Comparative Example 1 is substantially the same as that of Example 2, except that graphene oxide is used in Comparative Example 1 to replace the fluorinated modified graphene oxide.

[0024] Comparative Example 2: The operation of Comparative Example 2 is basically the same as that of Example 2, except that silicon carbide fiber is not added in Comparative Example 2.

[0025] Comparative Example 3: The operation of Comparative Example 3 is basically the same as that of Example 2, except that in Comparative Example 3, nano-silica is used to replace modified nano-silica.

[0026] Comparative Example 4: The operation of Comparative Example 4 is basically the same as that of Example 2, except that no fluorinated modified graphene oxide is added in Comparative Example 4.

[0027] Performance Test: Mechanical strength test: The tensile strength, bending strength and compressive strength tests were performed on the polytetrafluoroethylene material samples prepared in Examples 1 to 3 and Comparative Examples 1 to 4 using a universal material testing machine. The unfilled polytetrafluoroethylene material was set as a control group. The results are shown in Table 1 below.

[0028] Table 1. Mechanical strength test results of polytetrafluoroethylene materials

[0029] As shown in Table 1, the polytetrafluoroethylene material prepared by the present invention has excellent mechanical strength performance; as shown in Comparative Example 1 and Example 2, the graphene oxide lacks the fluorine atoms introduced by the fluorination modification, resulting in a weak interface bonding force between the graphene oxide and PTFE. Although the graphene oxide can still provide a certain reinforcement effect, its thermal conductivity and interface bonding force are weaker than those of the fluorinated modified graphene oxide, which may lead to a certain degree of influence on its tensile strength, bending strength and compressive strength; as shown in Comparative Example 2 and Example 2, although other fillers provide some reinforcement, the overall mechanical strength of the material is still significantly affected by the lack of the reinforcement effect of the fiber structure. As shown in Comparative Example 3 and Example 2, the interface bonding force of the unmodified nano-silica is weak, and the dispersion and mechanical properties of the filler are poorly improved, which may lead to poor impact resistance and bending resistance of the material; as shown in Comparative Example 4 and Example 2, the lack of fluorinated modified graphene oxide will affect the interface bonding force and mechanical strength of the composite material, resulting in a relative decrease in the tensile strength, bending strength and compressive strength of the material.

[0030] Corrosion resistance test: The polytetrafluoroethylene material samples prepared in Example 2 and Comparative Examples 1 to 4 were immersed in 98wt% concentrated sulfuric acid solution and 40wt% NaOH solution for 30 days, and the temperature was set to 80°C. The percentage change in tensile strength was tested on the 3rd, 7th, 14th and 30th days. The results are as follows: Figure 1 and Figure 2 The changes in sample appearance were recorded and the results are shown in Tables 2 and 3.

[0031] Table 2. Appearance changes of polytetrafluoroethylene materials in 98wt% concentrated sulfuric acid solution

[0032] Table 3. Appearance changes of polytetrafluoroethylene materials in 40wt% NaOH solution

[0033] Depend on Figure 1 , Figure 2The results of Table 2 and Table 3 show that the polytetrafluoroethylene material prepared by the present invention has no obvious performance and appearance degradation in the strong acid and strong alkali immersion tests, and exhibits good corrosion resistance. The results of Comparative Example 1 and Example 2 show that the change in tensile strength of Comparative Example 1 under acidic conditions is significant, which may be due to the fact that the graphene oxide has not been fluorinated and has weak interface bonding, making it susceptible to corrosion by acidic solutions, and then oxidized in an acidic environment, resulting in a rapid decrease in the tensile strength of the material and obvious peeling in appearance. The results of Comparative Example 2 and Example 2 show that the lack of the reinforcing effect of silicon carbide fibers The crack expansion and structural damage of the material in strong acid and strong alkali immersion are obvious, which leads to a significant decrease in tensile strength, and cracks and local peeling occur; from the results of Comparative Example 3 and Example 2, it can be seen that the surface of the nano-silicon dioxide has not been modified, which affects the interfacial bonding force of the material, resulting in obvious fading and slight cracking in an acidic environment, and a decrease in tensile strength; from the results of Comparative Example 4 and Example 2, it can be seen that the lack of the synergistic reinforcement effect of fluorinated modified graphene oxide leads to relatively weak interfacial bonding force of the material, which leads to a decrease in tensile strength and cracks and peeling on the surface of the material.

[0034] High temperature aging test: The polytetrafluoroethylene material samples prepared in Example 2 and Comparative Examples 1 to 4 were exposed to 300°C for 300 hours. The percentage change in tensile strength was measured at 50 hours, 100 hours, 200 hours and 300 hours respectively. The results are as follows: Figure 3 As shown, the aging phenomenon was checked at the same time, and the results are shown in Table 4.

[0035] Table 4. High temperature aging test results of polytetrafluoroethylene material samples

[0036] Depend on Figure 3From the results of Table 4, it can be seen that the polytetrafluoroethylene prepared by the present invention does not undergo obvious deformation at high temperature, and the change in tensile strength is small, and it has excellent heat resistance; from the results of Comparative Example 1 and Example 2, it can be seen that the surface of graphene oxide contains more oxygen groups, which affects its bonding force with PTFE, and at high temperatures, the stability of graphene oxide is poor, and thus it is easy to cause cracks, discoloration and the like on the surface of the composite material; from the results of Comparative Example 2 and Example 2, it can be seen that the lack of reinforcement of silicon carbide fiber, the strength and stability of the composite material at high temperature are poor, and deformation and cracks are prone to occur; from the results of Comparative Example 3 and Example 2, it can be seen that the dispersibility of unmodified nano-silicon dioxide is poor, which may lead to uneven surface of the composite material at high temperature, especially cracks, local warping and the like on the surface of the material at high temperature; from the results of Comparative Example 4 and Example 2, due to the lack of synergistic reinforcement of fluorinated modified graphene oxide, the interface bonding force of the material is relatively weak, and then the cracking and delamination phenomenon at high temperature is obvious.

[0037] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high temperature resistant and corrosion resistant polytetrafluoroethylene material, characterized in that: The composition includes the following raw materials in parts by weight: 50-60 parts of polytetrafluoroethylene, 5-10 parts of fluorinated modified graphene oxide, 3-5 parts of aluminum powder, 5-8 parts of modified silicon carbide fiber, 3-5 parts of silane-modified nano-silicon dioxide, 2-3 parts of polyphenylene sulfide, 2-3 parts of polyimide, 0.3-0.5 parts of dispersant and 0.5-1 parts of antioxidant; The specific preparation steps of the modified silicon carbide fiber are as follows: C1: Add 3-aminopropyltriethoxysilane to deionized water, stir and mix evenly, adjust the pH, and obtain a coupling agent solution; soak the silicon carbide fiber in the coupling agent solution and stir; C2: centrifuging, washing, filtering, and drying the silicon carbide fibers treated in step C1 at a relatively low temperature, and then heat treating at a higher temperature, and cooling to room temperature to obtain modified silicon carbide fibers; In step C1, the ratio of the amount of the silicon carbide fiber to the coupling agent solution is 1 g: 30-50 mL.

2. The high temperature resistant and corrosion resistant polytetrafluoroethylene material according to claim 1, characterized in that: The dispersant is any one of polyvinyl alcohol, polyacrylic acid and sodium dodecylbenzene sulfonate.

3. The high temperature resistant and corrosion resistant polytetrafluoroethylene material according to claim 2, characterized in that: The antioxidant is any one of tert-butylhydroquinone, tris(2,4-di-tert-butylphenyl)phosphate and 2,6-di-tert-butylphenol.

4. The high temperature resistant and corrosion resistant polytetrafluoroethylene material according to claim 3, characterized in that: The specific preparation steps of the fluorinated modified graphene oxide are as follows: A1: Add graphite powder to a flask, slowly add concentrated sulfuric acid and concentrated phosphoric acid, control the temperature, stir and disperse evenly, increase the temperature, and then slowly add potassium permanganate. After the addition is complete, increase the temperature, stir to react, slowly add deionized water to dilute, then add hydrogen peroxide, centrifuge, repeatedly wash with deionized water and HCl solution, and vacuum dry to obtain graphene oxide; A2: The graphene oxide prepared in step A1 is dispersed in anhydrous ethanol, and after being dispersed evenly by ultrasonic treatment, hydrogen fluoride gas is introduced to react, and the mixture is washed with deionized water to a neutral pH value, and dried to obtain fluorinated modified graphene oxide.

5. The high temperature resistant and corrosion resistant polytetrafluoroethylene material according to claim 4, characterized in that: In step A1, the ratio of the amount of the graphite powder, concentrated sulfuric acid and concentrated phosphoric acid is 1g:20-25mL:2-3mL; the ratio of the amount of potassium permanganate, deionized water, hydrogen peroxide and graphite powder is 3g:80-100mL:3-4mL:1g.

6. The high temperature resistant and corrosion resistant polytetrafluoroethylene material according to claim 5, characterized in that: In step A2, the ratio of the amount of graphene oxide to anhydrous ethanol is 2-5 mg:2 mL; the ratio of the amount of hydrogen fluoride gas to graphene oxide is 100-200 mL:1 g.

7. The high temperature resistant and corrosion resistant polytetrafluoroethylene material according to claim 6, characterized in that: The specific preparation steps of the silane-modified nano-silica are as follows: B1: Add nano-silica to anhydrous ethanol, perform ultrasonic dispersion treatment, and obtain a nano-silica dispersion; add γ-glycidyloxypropyltrimethoxysilane to anhydrous ethanol, stir and mix evenly, then slowly drop deionized water and acetic acid, stir and react, and obtain a coupling agent solution; B2: Slowly add the coupling agent solution prepared in step B1 to the nano-silica dispersion prepared in step B1, stir and react at room temperature, centrifuge, repeatedly wash with deionized water, and vacuum dry to obtain silane-modified nano-silica.

8. The high temperature resistant and corrosion resistant polytetrafluoroethylene material according to claim 7, characterized in that: In step B1, the ratio of the amount of the nano-silicon dioxide to anhydrous ethanol is 1 g: 40-50 mL; the ratio of the amount of γ-glycidyloxypropyltrimethoxysilane, anhydrous ethanol, deionized water and acetic acid is 1 g: 15-20 mL: 0.5-0.6 mL: 0.04-0.05 mL.

9. The high temperature resistant and corrosion resistant polytetrafluoroethylene material according to claim 8, characterized in that: In step B2, the volume ratio of the coupling agent solution to the nano-silicon dioxide dispersion is 0.02-0.03:

1.

10. A method for preparing a high temperature resistant and corrosion resistant polytetrafluoroethylene material according to any one of claims 1 to 9, characterized in that: The specific preparation steps of the polytetrafluoroethylene material are as follows: Ⅰ: drying the aluminum powder at 60-80°C for 1-2 hours, then heating it at 300-400°C for 1-2 hours, and naturally cooling it to room temperature to obtain pretreated aluminum powder; II: polytetrafluoroethylene, fluorinated modified graphene oxide, modified silicon carbide fiber, silane modified nano-silica, antioxidant, dispersant and pre-treated aluminum powder are sequentially added into the ball mill, polyphenylene sulfide and polyimide are added into the ball mill in three batches, and mixed at 200-300 rpm for 30-60 min; III: Pour the mixed raw materials in step II into a mold, heat to 150-200°C, apply a pressure of 10-15 MPa, maintain for 5-10 minutes, naturally cool to room temperature at room temperature, and then cure at 200-250°C for 1-2 hours to obtain a polytetrafluoroethylene material.

Citation Information

Patent Citations

  • Novel low-dielectric-constant PTFE-based composite material and preparation method thereof

    CN107722518A

  • Preparation method of silicon carbide-graphene-polytetrafluoroethylene composite material

    CN108794952A

  • Polytetrafluoroethylene composite material as well as preparation method and application thereof

    CN112812476A

  • Friction-reducing and wear-resisting composition, friction-reducing and wear-resisting composite material and preparation method and application thereof

    CN116535787A

Cited By

  • Wear-resistant cleaning cloth and preparation method thereof

    CN119913627A

  • Tire cloth liner with high-temperature-resistant coating and preparation method of tire cloth liner

    CN119928388A

  • High-temperature-resistant composite material as well as preparation method and application thereof

    CN120081648A

  • A high temperature resistant composite material and its preparation method and application

    CN120081648B

  • Bio-based wear-resistant fabric and preparation method thereof

    CN120096167A